English simplified - Ellsworth, Blanche; Higgins, John A. ([S.l.] : Longman, 2006)
English Simplified , 11/e - at only 72 pages - is a concise, inexpensive grammar handbook that continues to provide comprehensive coverage of grammar, punctuation, mechanics, spelling, word choice, and includes tips for ESL writers. The book also offers easy-to-read tables that clarify verb tenses and forms, the latest updates on documentation style, and material on note-taking, source evaluation, and avoiding plagiarism.